Potensi Biji Kolowe (Chydenanthus excelsus) Sebagai Pisisidal (Journal of Tropical Pharmacy and Chemistry, 2025)
Kolowe seeds (C. excelsus) has strong potential as piscicidal. Research conducted on the potential piscicidal bioindikator swamp eel fish (Synbranchus bengalensis Mc.Cllel), which is one of the pests in shrimp ponds. The piscicidal test results of kolowe seeds to S.bengalensis fish are fresh seed powder (LC50 = 305, 50 ppm); dry powder (LC50 = 315.35 ppm); crude methanol extract (LC50 = 345.20 ppm); frakasi n-Butanol extract (LC50 = 265.85) and the fraction of ethylacetate extract (LC50 = 650.90). The results are quite robust and selective as the most dominant secondary metabolites are saponins.